Application effect evaluation of hybrid biochemistry teaching model based on WeChat platform under the trend of COVID-19. Issue 9 (3rd March 2023) - Ding, Jianing; Ji, Xinye; Zhu, Kangle; Zhu, Huixia
Abstract : With WeChat platform as the carrier, we explored the effect of online and offline mixed teaching mode applied to Biochemistry teaching. One hundred and eighty-three students from the 4-year nursing major of Xinglin College of Nantong University in 2018 and 2019 were used as the observation group, using online and offline hybrid teaching methods, and 221 students majoring in 4-year nursing from Xinglin College of Nantong University in 2016 and 2017 were the control group, where the traditional classroom teaching method was adopted. The usual stage scores and final scores of the observation group were significantly higher than those of the control group ( P < .01). The micro-lecture videos, animations, and periodic assessment methods of the WeChat platform under "Internet+" can greatly stimulate students' interest in learning, thereby significantly improving academic performance and autonomous learning ability.